The importance of biogenic carbon storage in the greenhouse gas footprint of medium density fiberboard from poplar wood and bagasse - Seyedeh Masoumeh Hafezi (Elsevier, 2021)
Carbon storage in long-lived bio-based products is typically ignored or accounted for in a simplistic way in greenhouse gas (GHG) footprint calculations. We quantified the GHG footprint of medium density fiberboard (MDF) in Iran from poplar wood and bagasse, a by-product from sugarcane production. Inventory data was collected from sugarcane and poplar wood plantations and MDF factories in Iran during 2017–2019 to calculate cradle-to-grave footprints for 1 ​m3 of MDF. We quantify the effect of carbon storage, which depends on the crop rotation time and the economic lifetime of the product, with shorter rotation times and longer storage periods leading to lower footprints.Cradle-to-grave GHG footprints of poplar and bagasse-based MDF without accounting for biogenic carbon storage are 6.8·102 ​kg CO2-eq/m3 and 8.5·102 ​kg CO2-eq/m3, respectively. Footprints are higher for bagasse-based MDF than for poplar-based MDF because of a higher electricity use, higher resin use and larger transport distances in Iran. Taking into account carbon storage periods of 10–60 years decreases the footprints to 345–655 ​kg CO2-eq/m3 for poplar-based MDF and 292–771 ​kg CO2-eq/m3 for bagasse-based MDF. These results emphasize the importance of appropriately accounting for biogenic carbon storage in GHG footprint calculations of long-lived bio based products.